2002
DOI: 10.1161/01.hyp.0000022693.11752.e9
|View full text |Cite
|
Sign up to set email alerts
|

Genes and Family Environment Explain Correlations Between Blood Pressure and Body Mass Index

Abstract: Abstract-The correlations between systolic blood pressure (SBP) and diastolic blood pressure (DBP), and between SBP and body mass index (BMI), might result from genetic or environmental factors that determine variation in 2 or more phenotypes and are shared by family members. In 767 adult nuclear families (nϭ2912 individuals, including 66 pairs of monozygotic twins and 84 pairs of dizygotic twins), we used a multivariate normal model and the software FISHER to estimate genetic and environmental components of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
80
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 24 publications
11
80
0
3
Order By: Relevance
“…We are only aware of a couple of studies, which used twins to provide heritability estimates for body fat and blood pressure. A study by Cui et al 16 found that genetic variance accounted for 46% of the total variance in SBP and environmental variance accounted for 31% of the total variance. When they adjusted SBP for BMI there was only a small decrease in the variance, 2% for genetic and 14% for environmental.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are only aware of a couple of studies, which used twins to provide heritability estimates for body fat and blood pressure. A study by Cui et al 16 found that genetic variance accounted for 46% of the total variance in SBP and environmental variance accounted for 31% of the total variance. When they adjusted SBP for BMI there was only a small decrease in the variance, 2% for genetic and 14% for environmental.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results and others are hard to compare to the variance components analyses using only twins. 16,18,28 It may be that variance components analyses are not sensitive enough to determine these associations. There are some studies that have looked at specific gene effects, which may be common to blood pressure and body fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Thus, the recognition and management of elevated BP at an early age may be an important strategy for limiting the overall disease burden caused by hypertension. 4,5 Factors such as genetics, 6 diet 7 and physical activity 8 appear to contribute to elevated BP in children. In addition, population-based studies have consistently shown that overweight/obese children have higher levels of BP and a higher prevalence of hypertension than their non-overweight/obese counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence, using both segregation analysis and a whole genome scan techniques, supports an underlying genetic basis for these conditions. [42][43][44][45][46][47][48][49] While studies are underway to examine these linkages, more effort should be made to encourage African-American patients to comply with existing therapies. Promoting the use of antihypertensive medications in this population has been challenging at best.…”
Section: Discussionmentioning
confidence: 99%